EFL PRE-SERVICE TEACHERS' IDENTITY CONSTRUCTION DURING TEACHING PRACTICE PROGRAM - Indra Yoga Prawiro (Universitas Majalengka, 2021)
Professional teachers are an essential element in realizing the quality of education (Boyle, 2013). The teaching practice program is conducted as one of the training programs to become professional teachers for the pre-service teachers. During this program, EFL pre-service teachers begin to construct their teacher identity with various images of teachers. This case study explored the process of the pre-service teachers' identity construction from the perspective of sociocultural theory and the factors that contribute to the process. By distributing interviews and personal narratives to three EFL pre-service teachers in Wiralodra University, findings demonstrated that the process of pre-service teachers' identity construction is complex and personal. The teachers' identity construction involves both personal and social perspectives. From a personal perspective, it involves emotions and the self (self-image and self-esteem), and social perspective involves experiences and social interaction. This study also found that the preparation of materials and the choice of suitable methods and media for learning became challenges for the pre-service teachers. In addition, the pre-service teachers' identity construction is influenced by some factors. For example, they were mentoring and supervising, tensions, identity recognition, previous teaching experiences, pedagogy, content-area knowledge, relationship with students. That led to the development of pre-service teachers' identities.